An amorphous SiO2/4H-SiC(0001) interface: Band offsets and accurate charge transition levels of typical defects. (March 2015) - Li, Wenbo; Zhao, Jijun; Wang, Dejun
Abstract: A defect-free structural model of the amorphous SiO2 /4H-SiC(0001) interface is presented through first-principle calculations. Following the potential lineup method, we first calculate the valence- and conduction-band offsets of this interface, which are in good agreement with the experimental values. Based on this interface model, we create several typical interface defects and estimate the accurate charge transition levels of these defects within the HSE06 hybrid functional scheme. The results indicate that the silicon interstitial in SiO2 and carbon dimers in both SiC and SiO2 are the possible candidates for the large interface states experimentally observed near the conduction band of 4H-SiC. Abstract : Highlights: A new amorphous SiO2 /SiC interface model is generated using the first-principles method. Calculated valence- and conduction-band offsets of this interface are 2.84 eV and 2.76 eV, respectively. Accurate charge transition levels of several defects at the SiO2 /SiC interface are estimated. Silicon interstitial in SiO2 and carbon dimer can account for the large interface states experimentally observed.